INTERRELATIONSHIP BETWEEN FAMILY FARM INCOME, FARM SIZE AND FIELD CROP PRODUCTION STRUCTURE - Petar Munćan (Ekonomika Poljoprivrede (1979), 2011)
The greatest share of field crop production (88% оf corn, 73% wheat, 65% sunflower and about 50% of soybean and sugar beet production) in Serbia may be attributed to family farms. Efficiency of crop production will largely depend on the achieved yields and sale prices on one hand and the production costs on the other. Based on the results obtained, different economic indices can be expected contributing to the successfulness of farm management. Can the results obtained meet the needs of the producers depends on the social and economic ambience of the family farm. Afterall, depending on the income earned the producer will decide with regard to his future activities in the sector. Using the method of questionnaire the study focused on 24 family farms involved in field crop production in order to explore the impact of farm size and field crop production structure on the income achieved.